Synthesis of polyyne rotaxanes. - Movsisyan, L; Kondratuk, D; Franz, M; Thompson, A; Tykwinski, R; Anderson, H (2012)
Active-metal templating has been used to synthesize rotaxanes consisting of a phenanthroline-based macrocycle threaded around a C8, C12, or C20 polyyne chain. The crystal structure of the C12 rotaxane has been determined. In the rhenium(I) carbonyl complex of this rotaxane, with Re(CO)(3)Cl coordinated to the phenanthroline macrocycle, the proximity of the polyyne chain quenches the luminescence of the rhenium. These rotaxanes offer a new approach to controlling the environment and interactions of a polyyne chain.